2017
DOI: 10.1016/j.foodchem.2017.03.158
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid retention in biofortified maize using different post-harvest storage and packaging methods

Abstract: HighlightsDegradation rate of βCX was 51% lower than βC during storage of orange maize grain.Grain storage methods with 16% oxygen level reduced carotenoid degradation by 9.1%.Orange maize is an alternative to improve vitamin A status of deficient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 31 publications
13
62
0
Order By: Relevance
“…Our study confirmed the instability during grain storage of the nutritionally valuable carotenoids present in pVA biofortified orange maize, even without infestation (Mugode et al 2014;De Moura et al 2015;Bechoff and Dhuique-Mayer 2017;Taleon et al 2017). The pVA biofortified orange maize also sustained higher insect damage by 4 months' storage (69% damaged grains) compared to the white hybrid maize grain (37% damaged grains), despite identical numbers Fig.…”
Section: Shifts In Nutrient Contents In Insect-infested Cowpea Grainsupporting
confidence: 78%
“…Our study confirmed the instability during grain storage of the nutritionally valuable carotenoids present in pVA biofortified orange maize, even without infestation (Mugode et al 2014;De Moura et al 2015;Bechoff and Dhuique-Mayer 2017;Taleon et al 2017). The pVA biofortified orange maize also sustained higher insect damage by 4 months' storage (69% damaged grains) compared to the white hybrid maize grain (37% damaged grains), despite identical numbers Fig.…”
Section: Shifts In Nutrient Contents In Insect-infested Cowpea Grainsupporting
confidence: 78%
“…Retention values after 30 days at such degradation rates represented 65.0% for fermented chikwangue paste and 43.0% for fermented cassava microcossettes , at 24–27 °C. It is known that the rate of degradation of pVACs is relatively high in dry products, especially when the particle size of the product is small, due to its high surface area exposing the carotenoids to oxygen . Lower k values for fermented cassava paste suggest that carotenoids in an aqueous matrix are more stable than carotenoids exposed to oxygen in a dry matrix such as cassava microcossettes .…”
Section: Resultsmentioning
confidence: 99%
“…The k values for TC in cassava microcossettes were similar to values reported for C in dry cassava granules stored at 26-33 ∘ C (k = 0.0144-0.0271) by Bechoff et al 24 Retention values after 30 days at such degradation rates represented 65.0% for fermented chikwangue paste and 43.0% for fermented cassava microcossettes, at 24-27 ∘ C. It is known that the rate of degradation of pVACs is relatively high in dry products, especially when the particle size of the product is small, due to its high surface area exposing the carotenoids to oxygen. [25][26][27] Lower k values for fermented cassava paste suggest that carotenoids in an aqueous matrix are more stable than carotenoids exposed to oxygen in a dry matrix such as cassava microcossettes. These results are in concordance with previous studies showing that the main factor influencing degradation of carotenoids during storage of biofortified foods is oxygen availability.…”
Section: Estimation Of Degradation Kinetics Of Carotenoids In Cassavamentioning
confidence: 99%
“…Selection for PVA content has focused mostly on increasing BC; however, new evidence suggests that BCX may be more bioavailable (Howe and Tanumihardjo, 2006;Schmaelzle et al, 2014;Sugiura et al, 2014) and less susceptible to degradation than BC. Recent studies (Dhliwayo et al, 2014;Ortiz et al, 2016;Taleon et al, 2017;Sowa et al, 2017) suggested that breeding for PVA carotenoids should aim to increase BCX more than BC due to the increasing evidence of low stability of BC, higher BCX bioavailability compared to BC, and BCX's similar bioconversion and bioefficacy to BC (Schmaelzle et al, 2014), in addition to the genetic diversity found for BCX (Suwarno et al, 2015;Menkir et al, 2018). Breeding efforts have started in this regard and inbred lines have been developed and are currently being used in the development of new hybrids and synthetics.…”
Section: Breeding Provitamin A-enriched Maizementioning
confidence: 99%